1997
DOI: 10.1073/pnas.94.10.5213
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of meiotic double-strand breaks on yeast chromosome III

Abstract: In the yeast Saccharomyces cerevisiae, meiotic recombination is initiated by transient DNA double-strand breaks (DSBs) that are repaired by interaction of the broken chromosome with its homologue. To identify a large number of DSB sites and gain insight into the control of DSB formation at both the local and the whole chromosomal levels, we have determined at high resolution the distribution of meiotic DSBs along the 340 kb of chromosome III. We have found 76 DSB regions, mostly located in intergenic promoterc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
289
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(315 citation statements)
references
References 49 publications
23
289
0
2
Order By: Relevance
“…Alternatively, a delay in the onset of premeiotic S phase in the mutant might affect DSB formation. It is shown that premeiotic S phase is tightly coupled with the formation of meiotic DSBs (16,27). However, we think these indirect effects are unlikely.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternatively, a delay in the onset of premeiotic S phase in the mutant might affect DSB formation. It is shown that premeiotic S phase is tightly coupled with the formation of meiotic DSBs (16,27). However, we think these indirect effects are unlikely.…”
Section: Discussionmentioning
confidence: 98%
“…3K). Along the chromosome, DSBs are clustered around the middle part of both arms (16,21). rad6 reduced overall amounts of DSBs along the chromosome but did not change the distribution of DSBs.…”
Section: Gat1 (mentioning
confidence: 99%
“…For example, chromatin remodeling factors and histone modifications such as acetylation, methylation, and ubiquitination are involved in the meiotic alteration of the local chromatin structure at DSB sites (Sollier et al, 2004;Yamada et al, 2004;Yamashita et al, 2004;Mieczkowski et al, 2007). In addition, genome-wide studies have shown that DSB regions are distributed nonrandomly in DSB hot and cold domains (Baudat and Nicolas, 1997;Gerton et al, 2000;Borde et al, 2004;Blitzblau et al, 2007;Buhler et al, 2007) and that DSBs are formed preferentially in regions of chromatin loops (Blat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To uncover the regional regulation of Spo11, it is necessary to determine the chromosome-wide dynamic distribution of Spo11 in wild-type cells. Previous genome-wide studies of the Spo11 distribution along yeast chromosomes were performed in the rad50S-like mutant background, in which DSB ends are left unprocessed with covalently bound Spo11 (Alani et al, 1990), providing the map that does not taken into account the dynamic features of the process (Baudat and Nicolas, 1997;Mieczkowski et al, 2006Mieczkowski et al, , 2007Robine et al, 2007). The binding sites of Spo11 in rad50S-like mutants have been considered as DSB formation sites.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination in budding yeast is initiated by the formation of DSBs, a process which may be highly conserved among other organisms [13,14]. Depending on the size of genome, one meiotic nucleus may contain numerous DSBs [15] and recombinational repair of the DSBs occurs at the sites of initiation of synapsis, providing a way for pairing between homologous chromosomes [2,16,17].…”
Section: Genes Involved In Dsb Formation: Spo11 and Othersmentioning
confidence: 99%